A chatbot system to support visually impaired students: a pilot experiment - Padilha, Leonardo; Souza, Alinne C. Correa; Souza, Francisco Carlos M. (Anais da Escola Regional de Engenharia de Software (ERES); 2022: Anais da VI Escola Regional de Engenharia de Software, 2022)
Students with visual impairment need for different methods to assist their studies such as read tools and conversation bots (chatbots). Assistive technologies can be incorporated as a training or support tool and specifically in the educational field as complementary material. This paper proposes a chatbot as a study that supports an intelligent system for visually impaired students. Finally, the paper reports a pilot experiment regarding the effectiveness, time of response, and speech output of the proposed system in two scenarios of the software engineering area. Overall, the system proved to be tolerant of typing errors and returned quick responses by 0,9 seconds on average. Our results also demonstrate the efficiency in output with speech employing a library called gTTS.